Analysis of Elastohydrodynamic Lubrication Performance for TI Hourglass Worm Drive with Considering Tribo-dynamics Character - Zhu Yan; Liu Zaixin; Liao Honghui; Zhang Cui (Jixie chuandong)
The simple tribo-dynamics model for TI hourglass worm drive is proposed based on the load sharing theory and dynamic theory,which took the time-varying mesh stiffness,transmission error and friction coefficient of rough peak into account. The tribo-dynamics character is considered into line contact Elastohydrodynamic Lubrication（ EHL）. The meshing force and friction changes,oil film pressure and thickness distribution are obtained by calculation. The calculation results show that,when at low speed,the meshing force and friction of the tooth are larger than those at high speed. With the increase of the helix angle,the meshing forces both at inlet and outlet are obviously improved,and the friction of the tooth changes a little with the speed.Meanwhile,the maximum friction reduces,which can improve the transmission life of the worm drive pair. The meshing stiffness of the tooth has the greatest impact on oil film pressure and thickness,and the meshing force and friction coefficient of rough peak have less influence correspondingly.